Family-school digital communication: teacher perceptions on fostering family virtual participation. - Linde-Valenzuela, Teresa Loreto; Cívico-Ariza, Andrea; Colomo-Magaña, Ernesto; Linde-Valenzuela, Gema (My University, 2022)
The aim of this work justifies the relevance of the focus group in research focused on the recognition and promotion of innovative practices and educommunicative strategies that favour the media competence of families in emerging digital media to promote their virtual participation in the educational centre. The main objective is to identify measures, actions, and resources at the centre to train families and encourage virtual participation, to describe the social networks informing them between family-school, to define the factors that favour or hinder the use of ICT with families and to explore the teachers' perception of their need for training to interact and communicate with families. In other words, using a qualitative methodology and the focus group technique, the aim is to explore the teachers' perception of their knowledge and use of informal social networks in communication with families, and the actions they put into practice to promote their virtual participation in the dynamics of the school. The script is structured around four categories: measures and resources offered by the centre to train families, informal social networks used in the centres, factors that favour or hinder virtual participation, and the need for teacher training. With this technique, each participant is encouraged to express their perceptions, comment on their experience and teacher-family interaction through these media, establishing a personal approach with families and encouraging their virtual participation. The results of this work show the development of the methodology and the contents of the categories studied for the case analysed.
Communication numérique famille-école : perceptions des enseignants pour encourager la participation virtuelle de la famille
Keywords: Relaciones padres-profesores; Profesores - Formación profesional; Enseñanza - Innovaciones; Familia y enseñanza; Comunicación en educación; Tecnología educativa; Investigación cualitativa; Family-school relationship; Teacher education; Family involvement; Computer mediated communication; Family literacy; Focus group